Impact of climate change on wheat yield and quality in the Yellow River Basin under RCP8.5 during 2020–2050 - Xiao-Xu Long; Hui Ju; Jian-Dong Wang; Shi-Hong Gong; Guang-Yong Li (Advances in Climate Change Research, 2022)
Studying the impact of future climate change on the yield and quality of wheat in the Yellow River Basin (YRB) is both essential for rationalizing the utilization of climate resources and ensuring national food security. In this study, we employed corrected refined meteorological grid data (30 km × 30 km) generated by the Climate–Weather Research and Forecasting model under RCP8.5, coupled with the DSSAT–CERES–Wheat model to predict the impact of climate change on wheat phenology, yield, and grain nitrogen content (GNC) in the YRB from 2020 to 2050. According to the type of wheat variety and planting management in the YRB, we designed five wheat ecological regions (I–V). The results show that from 2020 to 2050, the agro-meteorological resource, involving temperature, solar radiation, and precipitation, would have an overall increasing trend during the wheat growth seasons in the YRB. The growth period of wheat was generally shortened by approximately 8 d, including 6 d less from sowing to anthesis, and 2 d less from anthesis to maturity. In general, the predicted wheat yield showed a decreasing trend in the YRB, with an average reduction of 0.19% over the period from 2020 to 2050 compared with the baseline period from 1975 to 2005, and the spatial variation in wheat yield change was considerably large. In the future, the Qing‒Zang Spring Wheat region (V) in the western part of the YRB would be the only region with a yield increase of 35.4%, whereas the Northern Spring Wheat region (I) in the northern part of the YRB would be the region exhibiting the greatest decrease of 9.9%. Moreover, compared with the baseline, the GNC would increase by an average of 2.3% in the YRB, with a significant increase in the southern and central parts during 2020–2050. The GNC increase in the Huang‒Huai Winter Wheat region (III) was the highest with a 12.5% increment, but the Qing‒Zang Spring Wheat region (V) is the only region where GNC would decline, with an average decrease of 18.9%. This study implies that wheat yield and GNC have a negative correlation constraint. In general, winter wheat yield is less affected by future climate change, and the GNC of winter wheat would increase more than that of spring wheat in the YRB. Tapping the potential pathway for the balance of yield and GNC improvements under future climate change needs more exploration in the future. For instance, appropriate adjustment of the irrigation and fertilizer schedules and regimes could be considered and recommended to ensure the simultaneous improvement of wheat yield and quality in the YRB.